Relationship between β-Thalassemia minor and Helicobacter pylori infection - Mohammad Zamani; Amin Vahedi; Ahmad Tamaddoni; Ali Bijani; Mojgan Bagherzade; Javad Shokri-Shirvani (Babol University of Medical Sciences, 2018)
Background: Until now, no study has been reported investigating the association between β-thalassemia minor and Helicobacter pylori (H. pylori) infection. This study was designed to compare H. pylori infection rate between β-thalassemia minor patients and healthy controls. Methods: A number of 100 β-thalassemia minor patients (50 males, 50 females) and 100 gender-matched healthy controls were prospectively recruited in this study in a period of 3 months. The study population consisted of the people who referred to a health center in Babol, North of Iran, for premarital counseling. H. pylori status was assessed by measuring the anti-H. pylori IgG antibodies using enzyme-linked immunosorbent assay. Demographic information and informed consent were collected from all participants. Results: The overall H. pylori infection rate was 43%. The infection was significantly more prevalent in thalassemia patients (53%) than in the controls (33%) in both univariate (OR=2.29, 95% CI: 1.3-4.06) and multivariable analyses (OR=2.05, 95% CI: 1.12-3.76). Age was the only significant factor which was positively correlated with the infection in β-thalassemia minor cases (OR=1.11, 95% CI: 1.02-1.2). Gender, blood groups, residency, and education level were not related to the infection. Conclusions: According to the results, it can be concluded that β-thalassemia minor patients are possibly more susceptible to H. pylori infection than healthy people. Further studies are needed to discover more about the exact mechanisms of increased susceptibility to H. pylori infection in β-thalassemia minor patients